2022
DOI: 10.1155/2022/3655543
|View full text |Cite
|
Sign up to set email alerts
|

A Successful Esthetic Approach of Gingival Depigmentation Using Microneedling Technique and Ascorbic Acid (Vitamin C)

Abstract: A gingival depigmentation is a periodontal plastic procedure that is performed in order to remove melanocytic pigmentation. A variety of different modalities have been proposed for removing hyperpigmentation involving surgical scraping, gingival autograft, cryotherapy, electrosurgery, and lasers. However, the microneedling technique is a nonsurgical procedure that creates microholes to facilitate the penetration of topical medications across the connective tissues. Case Description. A healthy female patient ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In our study, we established excellent aesthetic outcomes that are compatible with a case report that was done by Mostafa D, who applied AA to gingival mucosa using the MN technique, resulting in complete gingival depigmentation that lasted for six months [7]. Also, these results were in agreement with the clinical trial that was established by Yussif et al, who injected 1-1.5 ml of the AA (200-300 mg) intraepithelially in the gingival mucosa of 40 patients and identified a statistically significant reduction in the incidence of pigmentation and area of pigmentation with a mean of 0.737 [8].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, we established excellent aesthetic outcomes that are compatible with a case report that was done by Mostafa D, who applied AA to gingival mucosa using the MN technique, resulting in complete gingival depigmentation that lasted for six months [7]. Also, these results were in agreement with the clinical trial that was established by Yussif et al, who injected 1-1.5 ml of the AA (200-300 mg) intraepithelially in the gingival mucosa of 40 patients and identified a statistically significant reduction in the incidence of pigmentation and area of pigmentation with a mean of 0.737 [8].…”
Section: Discussionsupporting
confidence: 86%
“…Surgical techniques have shown early recurrence after 15 days to six months [30][31][32], while lower recurrence results were documented after 12-48 months when using laser and cryosurgery for GD [32][33][34]. On the other hand, recurrence of GP using ascorbic acid was reported in varying studies after six to nine months [7,8,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, neovascularization and neocollagenesis are introduced by the migration and proliferation of fibroblasts and the laying down of the intercellular matrix, which gives the tightening look of the mucosa (Fabbrocini et al, 2009 ; Majid et al, 2014 ). Furthermore, Mostafa and Alotaibi ( 2022 ) reported that MN with ascorbic acid was effective in gingival depigmentation, resulting in the healthy pink apperance of the gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…Melanin pigmentation in the oral cavity is classified differently according to its color degree, gingival position, and gingival color alteration [ 19 ]. In this study, preoperative assessment of each case was achieved using the GPI (gingival pigmentation index), in which scores were as follows [ 20 ]: 0 = absence of pigmentation.…”
Section: Methodsmentioning
confidence: 99%